Human alpha-aminoadipic semialdehyde synthase (AASS); A Target Enabling Package - Kopec, J (University of Oxford, 2018)
A description of the materials and methods is included within the TEP datasheet. This work provides the early tools to develop substrate reduction inhibitors for a genetic childhood seizure disorder, with the hypothesis to target the enzyme (AASS) upstream of the defective gene (ALDH7A1) in the human lysine metabolic pathway. This TEP package includes recombinant human AASS purification protocols, structures of the AASS second domain in different states, in vitro assays to detect ligand binding (differential scanning fluorimetry) and enzyme activity (NADH formation) of human AASS, as well as initial chemical matters.